Exploring Principal Leadership to Improve Swimming Achievement Through Qualitative Case Study at SD Benda 03 - Ma’mun, Syukron; Fakhruddin (Universitas Negeri Semarang, 2025)
This study explores the role of the school principal in enhancing swimming achievement among students at SD Negeri Benda 03, Brebes Regency. The research was motivated by a paradoxical phenomenon: despite limited facilities and resources, the school has produced notable achievements in swimming competitions. The objective of this qualitative case study was to analyze how school leadership, teacher collaboration, and parental support contribute to students' sports performance. Data were collected through in-depth interviews, observation, and documentation involving the principal, physical education (PJOK) teachers, students, and parents. The findings reveal that effective and transformational leadership by the principal played a critical role in mobilizing school resources, fostering collaboration among teachers, and establishing partnerships with external institutions. Additionally, committed teachers and proactive parental involvement emerged as essential in overcoming infrastructural limitations. The study concludes that strong, visionary school leadership, a supportive working environment, and engaged stakeholders collectively drive student achievement in sports. This research contributes to the educational leadership literature by providing contextual insights into how leadership and collaboration function in rural schools with limited resources, and offers practical recommendations for policy-makers and educators aiming to improve student outcomes in extracurricular domains.